Avaliação do efeito do volume da câmara de ar combinado com a frequência de bombeamento em um carneiro hidráulico - Dias, Lenon Costa (2020)
This work aimed to evaluate the effect of the volume variation of the air chamber combined with pumping frequency in a hydraulic ram, made of PVC, with a diameter of 1 '' at the inlet and ½ '' at the pump outlet in a situation of real installation in the countryside. Five different chamber volumes were used and a pump performance was evaluated for efficiency and maximum flow combined with different operating ranges. The adjustment of the impulse valve determined a frequency of pum ping of the hydraulic ram and it was possible to find an ideal frequency for each air chamber, which resulted in the best performance of the pump. The tests showed that influence the frequency of operation both in the repressed flow and in the efficiency of the hydraulic ram (CH), however there was no reduction in the volume of the air chamber in the CH efficiency. For chamber volumes less than 140mL there was a significant difference of flow rate in relation to larger air chambers, and from chamber 3 (380mL) there was little variation in performance parameters in agreement with other works in the area. It can then be considered that there is a minimum volume for construction of each hydraulic ram, being above that it should consider economic categories and margin of safety. The highest flow rate found was 0.938L / min for a frequency of 60 beats per minute from the impulse valve using chamber 3 (380mL) and the highest efficiency was found for chambers 1 and 3 with 57% for a frequency of 90 beats per minute. minute.